2020
DOI: 10.1177/1420326x20941220
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative effects of glass roof system parameters on energy and daylighting performances: A bi-objective optimal design using response surface methodology

Abstract: In regions with a hot-summer/cold-winter climate, a balance between energy-saving and better daylighting performance is often required for the design of a glass roof system. This research aims to reduce the total energy demand and to increase the useful daylight illuminance (UDI), by introducing a response-surface-methodology-based bi-objective optimization approach for three glass roof system models (no shading, exterior blinds, interior shades). Surrogate models were generated to quantify the effect of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…erefore, the combination of HCB + LC 3 +multi-Si is best suited for the building in the Indian context. Energy-efficient retrofitting in buildings has great potential to reduce GHG emissions [68,69]. tropical climatic buildings, green roof designs and reflective roofs (reflective coatings on roof surface) can be installed to reduce the ecological footprint of the building [47,66].…”
Section: Combined Effect Of Building Materials and Renewablementioning
confidence: 99%
“…erefore, the combination of HCB + LC 3 +multi-Si is best suited for the building in the Indian context. Energy-efficient retrofitting in buildings has great potential to reduce GHG emissions [68,69]. tropical climatic buildings, green roof designs and reflective roofs (reflective coatings on roof surface) can be installed to reduce the ecological footprint of the building [47,66].…”
Section: Combined Effect Of Building Materials and Renewablementioning
confidence: 99%
“…The study’s results revealed the effectiveness of that glazing technology in Saudi Arabia for being able to reduce annual energy consumption by 19% while maintaining efficient solar radiation providence in space. Yu and Leng [27] optimized the design of a glazed skylight to achieve both the lowest energy consumption and highest daylight performance using three approaches that relied on integrating shades, inner blinds, and exterior blinds systems to the glazed skylight. They used statistical analysis tools such as the analysis of variance (ANOVA), and regression method to uncover the optimal solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The RSM method offers an opportunity for building designers to optimize the design response by using a sequence of designed experiments (DOE) that will determine the relationship between input building parameters and the building design response. This approach has been successfully applied to model building consumption for improved energy efficiency in several studies, including EE retrofit optimization of schools [15], university buildings [16,21], office buildings [17], residential dwellings [18,20], and apartment buildings [19]. A summary of the studies utilizing RSM to predict building energy consumption is shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Although some of the studies from Table 1 Focused on energy performance prediction in non-residential buildings, they indeed provided a valuable reference for simulation approaches including the selection of potential building parameters for analysis. For example, the RSM simulations of energy consumption in education buildings [15,16,21] and offices [17] identified insulation thickness of the internal [16,21] and external walls [15,21], the heat transmission coefficient of the roofs [15], solar heat gain coefficient (SHGC) [15][16][17]21] and heat transfer coefficient of the external windows [15][16][17]22], roof heat transfer coefficient [16], internal and external shading coefficients [17,21] and window to wall ratio [15] as the key parameters affecting building energy efficiency. Similarly, for residential buildings the RSM simulations [18][19][20] pointed out heating and cooling system set-points [18,20], insulation thickness [18], SHGC [19], air infiltration rate [19], and insulation heat transfer coefficient [18][19][20] as the main contributors to energy savings.…”
Section: Introductionmentioning
confidence: 99%